2020
DOI: 10.1016/j.foodchem.2019.125715
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtus tomentosa (Aiton.): A review of phytochemistry, pharmacology and industrial applications research progress

Abstract: Rhodomyrtus tomentosa (Aiton) is a flowering plant native to southern and southeastern Asia.Up to date, 106 chemical constituents have been isolated and identified from R. tomentosa. Among these compounds, triterpenoids, flavonoids, phenols and meroterpenoids are the major constituents. Investigations of pharmacological activities of R. tomentosa revealed that this edible medicinal herb exhibits a wide range of therapeutic potential including antibacterial, antitumor, anti-inflammatory and antioxidant activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 61 publications
0
26
0
3
Order By: Relevance
“…According to the results of previous studies showed IL-1β and TNF-α can be inhibited by R. tomentosa, thereby decreasing the recruitment of eosinophils and neutrophils (27). The main compounds in R. tomentose include flavonoids, saponins, terpenoids (28). Flavonoid compounds have been shown to inhibit eosinophils by decreasing the production of IL-4 and IL-5 through the NF-κβ pathway (29).…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of previous studies showed IL-1β and TNF-α can be inhibited by R. tomentosa, thereby decreasing the recruitment of eosinophils and neutrophils (27). The main compounds in R. tomentose include flavonoids, saponins, terpenoids (28). Flavonoid compounds have been shown to inhibit eosinophils by decreasing the production of IL-4 and IL-5 through the NF-κβ pathway (29).…”
Section: Discussionmentioning
confidence: 98%
“…This condition causes a lot of misfolded insulin protein which will lead to the accumulation of misfolded insulin protein in the endoplasmic reticulum. This condition causes cell stress which leads to a cascade of oxidative stress [7,11]. Oxidative stress on pancreatic β cells will cause the activation of the inflammatory cascade, which will lead to the activation of death receptors and cause the death of pancreatic β cells [12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The novel skeletons of heteroterpenes, such as Rhodomyrtusials derived from terpenoid biosynthesis, have shown great potential in studies of antibacterial activities. Due to their novel and diverse structural skeletons, they are widely distributed in microorganisms, including fungi and actinomycetes, sponges, Myrtaceae, Ericaceae, Lamiaceae, and some large fungi such as Ganoderma lucidum (Matsuda and Abe, 2016;Peng and Qiu, 2018;Zhao et al, 2020).…”
Section: Nps Against Other Infectious Pathogensmentioning
confidence: 99%